A Nonisolated Single-Switch Coupled Inductor-Based DC-DC Converter with High Voltage Gain for Renewable Power Generation Systems - Hafez Nouhi; Vahid Talavat; Mohammad Farhadi-Kangarlu (International Transactions on Electrical Energy Systems)
This article proposed a new structure of nonisolated high step-up DC-DC converter based on a three-winding coupled inductor and voltage multiplier cells (VMCs) for renewable energy systems applications such as PV power generation. Continuous input current with low ripple, common ground between output and input ports, low voltage stress across semiconductors, low number of components, high voltage gain, and high efficiency are the main advantages of the proposed converter. In order to further increase the output voltage, the windings of the coupled inductor are combined with VMC. The combination of coupled inductor and VMC technique leads to a high voltage gain with low duty cycle, and therefore the conduction loss of power switch is reduced. Additionally, the diodes’ reverse recovery currents are reduced which improve the presented topology’s efficiency. On the other hand, the used VMCs clamp the voltage, and the peak voltages across power switch are decreased. The operational modes, steady-state, and efficiency analysis are discussed. Also, to demonstrate the performance of the recommended converter, an experimental prototype with 580 W output power and 400 V output voltage with the switching frequency of 25 kHz is built and the experimental results are presented. Also, another 1 kW, 400 V with the switching frequency of 50 kHz has been implemented and tested.